Upaya Deteksi Infeksi Jamur dan Pemanfaatan Audiovisual Mengenai Personal Hygiene Pada Pemulung dan Petugas Pengangkut Sampah - Rafika, Rafika; Pratma, Ridho; Arwin, Arwin; Sudirman, Putri Sri Saqinah; Artati, Artati (Poltekita: Jurnal Pengabdian Masyarakat, 2025)
Scavenger and dustman are jobs that has a lot of direct interactions with dry or wet waste, so there is a high risk of health problem if they don’t give more attention to their personal hygiene. One of diseases that can be the risk of their job is an infection of fungal found in waste that enter through their nails. The aim of activity is to detect fungal infections and provide knowledge of personal hygiene of scavenger and dustman. The activity was carried out of April-September 2023 in Manggala District and RT 3 of Tamangapa, Manggala District. Participants of this activity were 43 scavengers and dustman. The results of this activity shows the knowledge of personal hygiene of participants were increase after they got education and some of participants were infected by fungal on their nails. This activity needs follow-up by health workers at Manggala District to providing the knowledge of personal hygiene and skin disease caused by fungal infection that can affect the healthiness of participants.